2005
DOI: 10.1111/j.1467-6486.2005.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

An Action Pattern Model of Inter‐firm Cooperation*

Abstract: An action pattern model was developed and applied to the examination of inter-firm cooperative processes. The model considered cooperation as a continuous cycle of actions and reactions between cooperating partners. The building blocks of the model include cooperative equilibrium, disruptive events, action types and action patterns. Three action pattern variables were proposed to describe the interactions. It was hypothesized that action patterns are contingent on partner relationships and the transaction cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 84 publications
4
89
0
1
Order By: Relevance
“…It comprises a great variety of governance structures and has long experience with different forms of governance (Eccles, 1981;González-Díaz, Arruñada & Fernández, 2000;Lui & Ngo, 2005;Winch, 2001). It is not known for its institutional and technological innovativeness and experimentation but rather follows long-standing traditions of how it organizes and manages intra-and inter-organizational construction projects.…”
Section: Methods Sample and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It comprises a great variety of governance structures and has long experience with different forms of governance (Eccles, 1981;González-Díaz, Arruñada & Fernández, 2000;Lui & Ngo, 2005;Winch, 2001). It is not known for its institutional and technological innovativeness and experimentation but rather follows long-standing traditions of how it organizes and manages intra-and inter-organizational construction projects.…”
Section: Methods Sample and Data Collectionmentioning
confidence: 99%
“…In the context of the construction industry, Ngowi (2007) presents evidence that partner trustworthiness reduces the need for contractual safeguarding clauses. In their study in the Hong Kong construction industry, Lui and Ngo (2005) moreover find that trust enhances supplier acquiescence, i.e. suppliers are more inclined to follow the requests and actions of the buyer even at the expense of their own short-term interests.…”
Section: Selective Risk Managementmentioning
confidence: 99%
“…Whereas previous research examines how process, as well as structural, elements affect satisfaction with partners when cooperating (Lui & Ngo, 2005) the current paper examines how changes in group structure (same versus different groups) affect the cooperation processes individuals use to achieve collective action.…”
Section: Implications and Future Research Directionsmentioning
confidence: 99%
“…Though superficially obedient, the inferior party will protect its interests (Lui and Ngo, 2005). With interdependence, power is balanced, fostering an equal exchange relationship without negative feelings in which the two parties can purse mutual long-term benefits.…”
Section: Effect Of Interdependence On Opportunistic Behaviormentioning
confidence: 99%
“…Out of cost concerns, given high proprietary assets, franchisees will be less likely to adopt opportunistic behavior. Therefore, franchisees' idiosyncratic investments will inhibit their opportunistic behavior (Lui and Ngo, 2005). Williamson (1985) suggested that proprietary assets can modify firms' selfish motives and stabilize cooperation.…”
Section: Effect Of Idiosyncratic Investment On Opportunistic Behaviormentioning
confidence: 99%